2013
DOI: 10.3201/eid1904.121383
|View full text |Cite
|
Sign up to set email alerts
|

Feline Origin of Rotavirus Strain, Tunisia, 2008

Abstract: In Tunisia in 2008, an unusual G6P[9] rotavirus, RVA/human-wt/TUN/17237/2008/G6P[9], rarely found in humans, was detected in a child. To determine the origin of this strain, we conducted phylogenetic analyses and found a unique genotype constellation resembling rotaviruses belonging to the feline BA222-like genotype constellation. The strain probably resulted from direct cat-to-human transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…It is uncommon in people, and although a zoonotic origin is postulated (64,(79)(80)(81)(82)(83), it has not yet been convincingly proven whether such zoonotic strains spread among people. More recently, with the advent of advanced genome sequencing techniques and a more robust classification system (84), the possibility of G6 feline origin at some historical point has been proposed (16). With clustering of published human G6 genotypes with our feline G6 genotypes, rather than with published bovine G6 genotypes (85), our work strongly suggests that G6P [9] genotypes are examples of zoonotic or anthropozoonotic transmission between cats and people.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is uncommon in people, and although a zoonotic origin is postulated (64,(79)(80)(81)(82)(83), it has not yet been convincingly proven whether such zoonotic strains spread among people. More recently, with the advent of advanced genome sequencing techniques and a more robust classification system (84), the possibility of G6 feline origin at some historical point has been proposed (16). With clustering of published human G6 genotypes with our feline G6 genotypes, rather than with published bovine G6 genotypes (85), our work strongly suggests that G6P [9] genotypes are examples of zoonotic or anthropozoonotic transmission between cats and people.…”
Section: Discussionmentioning
confidence: 81%
“…Human RVAs with genetic homology to feline RVAs have been isolated from widespread geographical locations, including Japan (12,13), Israel (14,15), Tunisia (16), and the United States (17). Additionally, putative human/feline reassortant rotaviruses have been identified in children in Italy (18).…”
mentioning
confidence: 99%
“…G6P [9] was originally isolated from an Italian child with diarrhea [5] and has subsequently been reported in the United States [6], Hungary [7], Japan [8], Australia [14,15], and Tunisia [16]. The authors [8] considered that their isolates represented reassortment events between bovine-like human rotaviruses and human/feline AU-1-like rotaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequence and phylogenetic analyses (Tsugawa & Hoshino, 2008) as well as RNA-RNA hybridization under high stringency conditions (Nakagomi & Nakagomi, 2000) revealed that G3P [3] human rotavirus strains Ro1845 and HCR3A had emerged from direct transmission of a rotavirus strain indistinguishable from a feline strain Cat97 or a canine strain CU-1. Other examples have been provided recently: an Italian G3P [9] feline rotavirus, BA222 (Martella et al, 2011), shared a highly conserved although not exactly identical genotype constellation with human rotavirus strains KF17 detected in Japan (Yamamoto et al, 2011), 0537 in the USA (Grant et al, 2011), PAH136 andPAI58 in Italy (De Grazia et al, 2010), and 17237 in Tunisia (Fredj et al, 2013). Reflecting an increase of BA222-like rotaviruses detected in human children, it has been speculated that BA222 may represent a…”
Section: Introductionmentioning
confidence: 99%
“…While infection with feline rotavirus rarely causes severe illness in cats (Greene, 2006), feline rotaviruses are an infrequent source of human infections (Nakagomi & Nakagomi, 1989;Matthijnssens et al, 2011;Fredj et al, 2013). Whole genome sequence and phylogenetic analyses (Tsugawa & Hoshino, 2008) as well as RNA-RNA hybridization under high stringency conditions (Nakagomi & Nakagomi, 2000) revealed that G3P [3] human rotavirus strains Ro1845 and HCR3A had emerged from direct transmission of a rotavirus strain indistinguishable from a feline strain Cat97 or a canine strain CU-1.…”
Section: Introductionmentioning
confidence: 99%